2018
DOI: 10.1111/jocn.14487
|View full text |Cite
|
Sign up to set email alerts
|

Application of instant messaging software in the follow‐up of patients using peritoneal dialysis, a randomised controlled trial

Abstract: Internet-based follow-up by instant messaging software appears to be a feasible and acceptable method of delivering peritoneal dialysis treatment for patients with end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(116 citation statements)
references
References 25 publications
0
100
0
Order By: Relevance
“…28,30 Three studies reported phosphate levels with one showing lower levels of phosphate. 25 The others showed no significant difference, 28 with one compared with a control group and another comparing rates pre- and post-intervention. 32 Two studies also reported no significant difference in levels of creatinine compared with a control group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…28,30 Three studies reported phosphate levels with one showing lower levels of phosphate. 25 The others showed no significant difference, 28 with one compared with a control group and another comparing rates pre- and post-intervention. 32 Two studies also reported no significant difference in levels of creatinine compared with a control group.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies, representing 1334 participants receiving PD, were included in the review. Of these, five were RCTs, 25 29 while one was a non-RCT. 30 Of the other included studies, six were pre versus post designs 31 36 and three had no comparison (observational studies with only follow-up measures).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations